The Quality Effect of Auditing on Tax Compliance: Evidence from Tunisian Context - Soltani, Lynda (International Journal of Economics and Financial Issues, 2022)
Taxation is the subject of complex and evolving regulations. it has become one of the major concerns of any business to better manage its finance, the responsible for corporate governance give an importance to the fiscal in the strategy and management of the company. In recent years, the importance of taxation in the financial and accounting environment is motivated to study the impact of control and transparency of infomation affected by audit quality. We study a sample of 19 companies between 2013 and 2017, the result shows that audit quality improves tax compliance in the Tunisian context while measuring tax evasion by the difference between the statutory tax rate and the effective tax rate. This study finds that tax evasion in Tunisian firms may have decreased with better audit quality.